Role of klotho and fibroblast growth factor 23 in arterial calcification, thickness, and stiffness: a meta-analysis of observational studies - Citrawati Dyah Kencono Wungu; Hendri Susilo; Mochamad Yusuf Alsagaff; Bendix Samarta Witarto; Andro Pramana Witarto; Cennikon Pakpahan; Arief Gusnanto (Scientific Reports, 2024)
Abstract This meta-analysis was conducted to clarify the role of klotho and fibroblast growth factor 23 (FGF-23) in human arterial remodeling across recent studies, in terms of arterial calcification, thickness, and stiffness. A systematic literature search was conducted on five databases for articles up to December 2023. Arterial calcification, thickness, and stiffness were determined using the calcification score and artery affected, carotid intima–media thickness (CIMT), and pulse wave velocity (PWV), respectively. Sixty-two studies with a total of 27,459 individuals were included in this meta-analysis. Most studies involved chronic kidney disease patients. Study designs were mostly cross-sectional with only one case–control and nine cohorts. FGF-23 was positively correlated with arterial calcification (r = 0.446 [0.254–0.611], p < 0.0001 and aOR = 1.36 [1.09–1.69], p = 0.006), CIMT (r = 0.188 [0.02–0.354], p = 0.03), and PWV (r = 0.235 [0.159–0.310], p < 0.00001). By contrast, Klotho was inversely correlated with arterial calcification (r = − 0.388 [− 0.578 to − 0.159], p = 0.001) and CIMT (r = − 0.38 [− 0.53 to − 0.207], p < 0.00001). In conclusion, FGF-23 and Klotho were associated with arterial calcification, thickness, and stiffness, clarifying their role in arterial remodeling processes.